The Role of Adaptive Management in the Resilience and Growth of Small and Medium Size Enterprises - Saah, Paul; Mbohwa, Charles; Madonsela, Nelson Sizwe (International Review of Management and Marketing, 2024)
Small and Medium Size Enterprises (SMEs) are the backbone, and the main stimulus of development, and studies demonstrate that these businesses play an essential role in the economic growth of the global economy. Adaptive management is a crucial approach for enhancing the resilience and growth of SMEs in today’s dynamic and unpredictable business environment. The purpose of this study is to determine the role of adaptive management in the resilience and growth of SMEs. A qualitative technique was employed as the research method in this study to collect and analyze data to ascertain the role of adaptive management in the resilience and growth of SMEs. The population of this study constitutes SME owners and managers within South Africa and a straightforward random selection process was used to choose the 20 of them to participate in the study. Atlas ti was used to code and analyze transcripts, produce network diagrams, and visualize data. It is evident from the findings of this study that poor management in an enterprise would inevitably result in the failure of the business. This implies that SMEs that embrace adaptive management principles demonstrate a higher capacity to navigate through uncertainties and capitalize on emerging opportunities, thus fostering resilience and sustainable growth. This suggests that for small businesses to succeed, SME owners and the government should collaborate to find solutions to most managerial problems faced by businesses so that the enterprises can grow and be sustainable.